Yeast GSK-3 kinase regulates astral microtubule function through phosphorylation of the microtubule-stabilizing kinesin Kip2 - Drechsler, Hauke; Na Tan, Ann; Liakopoulos, Dimitris (Journal of cell science, 2015)
The S. cerevisiae kinesin Kip2 stabilises astral microtubules (MTs) and facilitates spindle positioning through transport of MT-associated proteins, such as the yeast CLIP-170 homologue Bik1, dynein and the adenomatous-polyposis-coli-related protein Kar9 to the plus ends of astral MTs. Here, we show that Kip2 associates with its processivity factor Bim1, the yeast homologue of the plus-end-tracking protein EB1. This interaction requires an EB1-binding motif in the N-terminal extension of Kip2 and is negatively regulated by phosphorylation through Mck1, the yeast glycogen synthase kinase 3. In addition, Mck1-dependent phosphorylation decreases the intrinsic MT affinity of Kip2. Reduction in Kip2 phosphorylation leads to stabilisation of astral MTs, and accumulation of Kip2, dynein and Kar9 at MT plus ends, whereas loss of Mck1 function leads to defects in spindle positioning. Furthermore, we provide evidence that a subpopulation of Mck1 at the bud-cortex phosphorylates Kip2. We propose that yeast GSK-3 spatially controls astral MT dynamics and the loading of dynein and Kar9 on astral MT plus ends by regulating Kip2 interactions with Bim1 and MTs.
Gesehen am 29.06.2020